GOOD INTENTIONS: OTHERING LGBTQ LITERATURE FOR CHILDREN AND YOUNG ADULTS IN THE SLOVENIAN LITERARY SYSTEM (Philological Studies, 2021)
The article looks at the position of LGBTQ literature for children and young adults in the Slovenian literary system. In particular, it attempts to demonstrate that LGBTQ texts are often written, understood and didacticized with (implicit) reference to difference, empathy, acceptance and otherness. It analyses literary and critical texts with a focus on the apparently well-meaning processes of othering found at the levels of plot, character, writers’ didactic interference, critical reception and publishing. These processes influence how the members of the in-group perceive the members of the out-group (both of whom can be readers and writers) and how each see themselves. Not only do they reflect, but they also help shape reality and impact on the ways individuals are treated in society. Therefore, the criteria of literariness, though essential, are not absolute, and all agents in the children’s and young adult literary system should take account of the human/children’s right to inclusion.
Keywords: LGBTQ literature for children and young adults, othering, exclusion, children’s rights, empathy, pedagogy